Various Dimensional CuI–DPA Coordination Polymers Based on the Same Components for Different Electronic and Photothermal Properties. Issue 7 (27th April 2022) - Fan, Hong-Chuan; Xia, Xin; Zeng, Yan-Bo; Wang, Qiu-Feng; Chen, Dan; Qin, Shi-Chun; Wang, Chun-Qiong; Cao, Qiu-E; Zheng, Li-Yan
Abstract : Constructing varied dimensional coordination polymers (CPs) from the same chemical components is interesting but rare, which holds back to building the relationship between spatial topological structures and properties. Designing ligands with unequal coordination sites is a possible strategy to construct CPs with distinct spatial topologies. Herein, a novel planar ligand 2, 7‐di(pyridin‐4‐yl)acridine (DPA) with two kinds of coordination N sites is prepared for coordinating with copper(I) iodide (CuI). 1D‐, 2D‐, and 3D‐CPs (named α‐, β‐, and γ‐CuI–DPA, respectively) are constructed by similar [Cu2 I2 ] dimers and DPA building blocks but different CuI‐to‐DPA ratios. Interconversions among three CPs are verified. According to property characterization and structural analysis, 3D γ‐CuI–DPA with unique chains possesses charge movement pathways for higher electrical conductivity than those of the others. In addition, π–π stacking interactions are observed to play a significant role in promoting nonradiative migration and triggering photothermal conversion. This work presents a set of objects for investigating the structure‐to‐property connection of CPs in conductivity and photothermal conversion, as well as a roadmap for designing potential functional CPs materials in future. Abstract : The interconversion among 1D α‐CuI–DPA, 2D β‐CuI–DPA and 3D γ‐CuI–DPA is based on the same reactants CuI and DPA. Distinct spatial topologies result in different properties. 3D γ‐CuI–DPA shows the best conductivity and photothermal conversion ability.